Gender-Specific Outcomes of Musical Preferences and Interventions for High Blood Pressure among Selected Adults in Ago-Iwoye - Akande, Sunday Olufemi (Journal of Gender and Power, 2024)
Hypertension is a prevalent health issue among Adults, necessitating effective management strategies. Music therapy has shown promise in reducing blood pressure, but gender differences in its efficacy remain understudied. This study investigated gender-specific outcomes of musical interventions on high blood pressure among selected Adults in Ago-iwoye. It elucidates aptly on factors responsible for high blood pressure. This quasi-experimental study involved 20 adults (10 males, 10 females) with hypertension. Participants were randomly assigned to either a music intervention group (30 minutes of relaxing music, twice weekly, for 4 weeks). Blood pressure measurements were taken at baseline, 4 weeks. Results showed significant reductions in systolic and diastolic blood pressure in both males and females in the music intervention group. However, the preferred music genre for both male and female differ. Conversely, musical preferences are significant in the outcome of the musical intervention on participants. This study highlights the effectiveness of musical interventions in reducing high blood pressure among adults, with gender-specific differences in outcomes. These findings inform tailored hypertension management strategies for adults and recommended the development of personalized hypertension management programme, particularly in local settings, and underscore the importance of considering gender differences with individual musical genre preferences in the design of music-based interventions.